Editorial to the Special Issue “Recent Advances in Biochemical Mechanisms of Acute Myeloid Leukemia” - Maria Mesuraca; Clelia Nisticò; Emanuela Chiarella (Biomedicines, 2023)
Acute myeloid leukemia (AML) is a clonal malignant disorder of myeloid progenitor cells characterized by uncontrolled proliferation, dysregulation in the differentiation program, and inhibition of apoptosis mechanisms [...]